Strongly fluorescing silver(I) complex of a new thiadiazole ligand: X-ray crystallography, close anagostic interactions and TD-DFT emissive states - Demir, Serkan; Gür, Mahmut; Şener, Nesrin; Şener, İzzet; Alpaslan, Gökhan (Informa UK Limited, 2019)
A new thiadiazole ligand, N-ethyl-5- (benzo[b]thien-2-yl-)-1,3,4-thiadiazol-2-amine (BTH), was prepared from 3-methyl-1-benzofuran-2-carboxylic acid and N-ethylhydrazinecarbothioamide precursors. C...
Keywords: anagostic interaction; Thiadiazole ligands; silver(I) complex; excited state calculations; photophysical properties